Factors influencing students' learning willingness in online art classroom of Chengdu Private University - Zhang, Jingzhi; Phongsatha, Satha (วารสารนวัตกรรมการศึกษาและการวิจัย, 2024)
In this study, students majoring in art design who participated in online art classes in Chengdu Private University were selected as research objects to study the factors influencing students' willingness to learn behavior. The factors studied in conceptual framework included perceived usefulness (PU), performance expectancy (PE), behavioral intention (BI), satisfaction (SA), self-efficacy (SE), social influence (SI), as well as perceived behavioral control (PBC). Research design, data and methodology: After data collection, 512 questionnaires were collected and after review for validation, 500 questionnaires remain for the data analysis. Purposive sampling and quota sampling were used in the sampling procedures. Before the data gathering, the content validity and reliability of questionnaire was tested by Item-Objective Congruence (IOC) and pilot test (n=30). After the data collection, the Structural equation model (SEM) and confirmatory factor analysis (CFA) are used in combination to verify the verification hypothesis and goodness of fit of the model studied. Results: According to the seven hypotheses, it is found that the main factor affecting students' willingness is the perceived behavioral control (PBC).